PEMBEKALAN APLIKASI ONLINE DENGAN MEDIA GOOGLE CLASSROOM “MITRA KREATIF COMPUTER” KISARAN - Edward Robinson Siagian (Jurnal Pemberdayaan Masyarakat, 2024)
Community Service Activities are carried out at the Kisaran "Mitra Creative Computer" Business Management Education Center in the form of providing online applications using the Kisaran "Mitra Creative Computer" google classroom media to students at junior high and high school/equivalent levels in the Kisaran area. Previously, the Kisaran "Mitra Creative Computer" Business Management Education Center provided learning and training materials to the community with various skills such as graphic design training, computer engineering and others. The training that will be carried out is providing online applications using the Kisaran "Mitra Creative Computer" Google Classroom media to junior and senior high school students in the Kisaran area. With this training course, it can help people to get jobs or open business opportunities. Evaluation of learning outcomes is carried out directly after the training is completed, by giving exam questions or quizzes by setting the time tempo. The questions/quizzes are in the form of design examples and will be worked on by each participant, then saved and displayed on the projector, then the instructor gives a score and submits the score to the admin of the Kisaran "Mitra Creative Computer" Business Management Education Center to print a certificate and give it to training participants